Editorial – Using sexual identity labels to move beyond them - das Nair, Roshan (British Psychological Society, 2010)
This is the first issue of the Psychology of Sexualities Review. As mentioned in my previous Editorial, this change in name reflects the change made to the Section’s name, following a ballot of the Section’s membership. I trust that the papers in this issue are a testament to the Editorial Team’s promise to continue the legacy of the Lesbian & Gay Psychology Review’s of publishing high quality papers. In this Editorial I focus on the idea of using sexual identity labels, which have served us well and continue to do so, to move beyond them. I must clarify that by suggesting movement beyond these labels, I am in no way implying that we discard them, but permit a flexibility to incorporate other labelled identities and label-less identities to the fold. This plurality and inclusivity, I believe, forms the spirit of the Psychology of Sexualities Review. When thinking about plurality and inclusivity related to sexuality, two landmark judicial judgments in the recent past come to mind, perhaps because of their personal relevance to me, both from my own subject-ship and from those of some of my clients I see in therapy. The first, the Delhi High Court’s reading down of Section 377 of the Indian Penal Code, a section which criminalises private consensual sex between adults of the same sex (reported in the papers as ‘India decriminalises gay sex’, Mitta & Singh, 2009); and the second, the UK Supreme Court ruling related to ‘gay asylum seekers’ (‘Gay asylum seekers’, 2010). There is no question about the importance, the worthiness, the triumph, and the desperate need for both these judgments. A close reading, however, examining the language used in the official judgments and the English language newspaper reporting of these, exposes a certain conservative economy of terms that both reports employ. This is particularly pertinent as both judgments are related to minorities from India, and ‘gay asylum seekers’ from Cameroon and Iran, countries where some sexual minorities2 do not identity as ‘gay’ or even ‘homosexual’. The collapsing of sexual identities (and associated labels) into seemingly ‘neutral’ terminology employing behavioural categories of ‘men who have sex with men’ (MSM) and ‘women who have sex with women’ (WSW) is also problematic. While such usage has almost become the mainstay of epidemiological and public health studies (since the 1990s), social constructionists have highlighted the limits of such terms, but have also critiqued the use of identity labels such as ‘gay’, instead arguing for a ‘more textured understandings of sexuality that do not assume alignments among identity, behaviour, and desire’ (Young & Meyer, 2005, p.1144). My argument is that just as terms such as MSM and WSW tend to obliterate self-determination regarding sexual identities, terms such as ‘gay’ and ‘lesbian’, when applied indiscriminately or as global categories, can be as alienating; obfuscating text and subtext of sexual identities, desires, and practices. These terms then have the potential to become essentialist concepts.